Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3892/ol.2018.9758
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin regulates tumor aggressiveness under acidosis condition in breast cancer cell lines

Abstract: Breast cancer progression is composed of multiple steps that are influenced by tumor cell adaptations to survive under acidic conditions in the tumor microenvironment. Regulation of this cell survival behavior is a promising strategy to avoid cancer development. Melatonin is a natural hormone produced and secreted by the pineal gland capable of modulating different biological pathways in cancer. Although the anti-cancer effects of melatonin are currently widespread, its role in the acid tumor microenvironment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Melatonin was able to decrease GLUT1 protein expression levels in both cell lines, both at normal (7.2) and acidic pH (6.7). It was concluded that melatonin treatment increases apoptosis and decreases proliferation and GLUT1 protein expression under acute acidosis conditions in breast cancer cell lines [108] (Table 2).…”
Section: Melatoninmentioning
confidence: 99%
“…Melatonin was able to decrease GLUT1 protein expression levels in both cell lines, both at normal (7.2) and acidic pH (6.7). It was concluded that melatonin treatment increases apoptosis and decreases proliferation and GLUT1 protein expression under acute acidosis conditions in breast cancer cell lines [108] (Table 2).…”
Section: Melatoninmentioning
confidence: 99%
“…Melatonin (MT) has been postulated to be an antiestrogenic agent, so it should be strongly considered, at least in the treatment of the same cohorts of BC patients that can benefit from antiestrogens [ 280 , 281 ]. In BC cell lines, treatment with MT decreases tumor aggressiveness and increases apoptosis [ 282 ]. MT plays a number of other different actions as an anti-cancer agent [ 283 ].…”
Section: Other Ph-related Available Therapies In Breast Cancer Trementioning
confidence: 99%
“…Cell viability was evaluated under acidosis conditions by MTT assay, using 4-morpholine-ethanesulfonic acid to produce a pH value of 6.7 24,25 . Cells were treated with selected chalcones 11 and 17 at their respective IC 50 values.…”
Section: Antiproliferative Activity Of Selected Chalcones 11 and 17 Umentioning
confidence: 99%